Neoadjuvant short-course radiotherapy or chemoradiation plus consolidative chemotherapy followed by radical operation for locally advanced rectal cancer - Lee, Shing Fung; Yip, Pui Lam; Wo, Barry; Wong, Natalie Sean-Man; Vellayappan, Balamurugan A.; Mamon, Harvey J.; Lee, Francis Ann Shing (Frontiers in Oncology, 2024)
Limited evidence compares short-course radiotherapy (SCRT) and long-course chemoradiation (LCCRT), both followed by consolidative chemotherapy before radical rectal surgery. We conducted a retrospective cohort study to assess treatment response, survival outcomes, and toxicity in patients with locally advanced rectal cancer.Patients (cT3-4 and/or N+) treated with SCRT or LCCRT, consolidative chemotherapy, and total mesorectal excision between 2013-2021 were identified. Cause-specific cumulative incidence of disease-related treatment failure, locoregional recurrence, distant metastases, and overall survival were evaluated using flexible parametric competing risk analysis and Kaplan-Meier methods, adjusted for treatment regimens and clinicopathological factors. Pathological complete response (pCR), tumour downstaging, and toxicity were reported.Among 144 analysed patients, 115 (80%) underwent curative rectal surgery. LCCRT and SCRT groups achieved pCR in 10 (18%) and 7 (12%) patients, respectively (odds ratio, 1.68; 95% confidence interval [CI], 0.59-4.78). The adjusted cause-specific hazard ratio for disease-related treatment failure with LCCRT versus SCRT was 0.26 (95% CI, 0.08-0.87). Three-year cumulative probability of diseaserelated treatment failure was 10.0% for LCCRT and 25.6% for SCRT. No significant differences in Tdownstaging, N-downstaging, significant pathologic downstaging (ypT0-2N0), locoregional failure, distant metastasis, or overall survival were found. Late rectal toxicity occurred in 10 (15%) LCCRT and 2 (3%) SCRT patients.LCCRT with consolidative chemotherapy demonstrated improved disease-related treatment failure compared to SCRT, despite higher late rectal toxicity. Further research is needed to assess long-term oncologic outcomes and toxicity.